Nalar Maqasid al-Syari'ah Rasyid Ridha dalam Tafsir Al-Manar: Studi atas Ayat-Ayat Riba dan Poligami - Saifullah Saifullah (Jurnal Antologi Hukum, 2026)
The stagnation of Islamic law has been largely attributed to rigid textualism and taqlīd that disconnects revelation from evolving social realities. This normative-ushuli study aims to examine the maqāṣid al-sharī‘ah paradigm independently developed by Muhammad Rashid Rida in the later volumes of Tafsir Al-Manar (Volumes VI-XII) through content analysis and legal hermeneutics. The findings reveal that Rida constructed a legal epistemology based on a dichotomous distinction between the static sphere of worship (ta‘abbudī) and the dynamic realm of social transactions (ta‘aqqulī). In socio-economic matters, the principle of maslahah mursalah is positioned as a primary methodological instrument for qualifying the general application of hadith āhād. This teleological reasoning is demonstrated in two major cases: the reinterpretation of riba by restricting its absolute prohibition to ribā al-nasī’ah, thereby opening the possibility of re-examining modern banking interest through a maqāṣid-based approach, and the restriction of polygamy through state legal intervention to protect women’s rights and family welfare. The study further demonstrates that the legal paradigm developed in Tafsir Al-Manar possesses significant relevance to contemporary Islamic legal reform, particularly in the fields of family law and Islamic economic law in Indonesia.